Determination of solubility parameters for organic semiconductor formulations - Machui, Florian; Abbott, Steven; Waller, David; Koppe, Markus; Brabec, Christoph (Macromolecular Chemistry and Physics, 2011)
The concept of Hansen solubility parameters (HSP) is applied to organic semiconductors in order to determine and predict their solubility behavior, which is essential for the design of functional and environmentally friendly ink formulations for organic photovoltaics. Two different conjugated polymers, one semicrystalline and one dominantly amorphous, and one fullerene derivative are selected as prototype candidates to evaluate the applicability of the HSP concept for organic semiconductors. The method for determining the solubility parameters is described and the quality of the HSP fits as well as their suitability for designing of organic electronic inks are discussed in detail. The applicability of Hansen solubility parameters in designing organic semiconductor ink formulations is analyzed by determining and predicting the solubility behavior of three different organic semiconductors. A large number of solvents are studied and temperature-dependent solubility is examined to enhance the practical relevance of this work. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: conjugated polymers; fullerenes; Hansen solubility parameters (HSP); ink formulations; organic photovoltaics